2011
DOI: 10.1177/0969733011408169
|View full text |Cite
|
Sign up to set email alerts
|

Perceived ethical values by Iranian nurses

Abstract: Nursing, a scientific and practical discipline, faces continuing challenges of finding new direction in order to decipher its core values and develop current ethical codes for nursing practice. In 2009-10, 28 nurses were purposely selected and interviewed using a semi-structured format in focus groups and individually. Thematic Content Analysis helped explore the perception of Iranian nurses on ethical values in patient care. Seven major themes emerged: respect for dignity, professional integrity, professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
96
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 32 publications
6
96
0
2
Order By: Relevance
“…Con el fin de conocer la percepción de las enfermeras sobre la aplicación de lo establecido en los títulos I y II del Código Deontológico de Enfermería en Colombia, se planteó esta investigación, cuyos resultados pueden contribuir a promover en los planes de formación, la sensibilidad ética y la capacidad para el raciocinio moral 8,9 ; aunque las autoras reconocen que puede estar subestimadas y sobreestimadas las respuestas de los participantes debido a lo abstracto del tema como lo es la ética 10 , por ello consideran que quizás el mejor diseño sería un estudio de seguimiento que incluyera la observación de las actitudes y comportamientos éticos de las enfermeras en la práctica asistencial.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Con el fin de conocer la percepción de las enfermeras sobre la aplicación de lo establecido en los títulos I y II del Código Deontológico de Enfermería en Colombia, se planteó esta investigación, cuyos resultados pueden contribuir a promover en los planes de formación, la sensibilidad ética y la capacidad para el raciocinio moral 8,9 ; aunque las autoras reconocen que puede estar subestimadas y sobreestimadas las respuestas de los participantes debido a lo abstracto del tema como lo es la ética 10 , por ello consideran que quizás el mejor diseño sería un estudio de seguimiento que incluyera la observación de las actitudes y comportamientos éticos de las enfermeras en la práctica asistencial.…”
Section: Discussionunclassified
“…Los hallazgos de este estudio son similares a uno llevado a cabo con enfermeras Iraníes donde se indagó la percepción que estas tenían sobre los valores éticos en la atención al paciente 10 . Este estudio empleo una metodología cualitativa y en él se encontró siete temas principales: el respeto por la dignidad, la integralidad de la práctica, compromiso profesional, el desarrollo de relaciones humanas, la justicia, la honestidad y la integralidad, e intento para promover las competencias profesionales e individuales, aspectos que las enfermeras del actual estudio percibieron que se cumplían en un gran porcentaje y que corresponde al Título I del Código Deontológico de Enfermería en Colombia.…”
Section: Discussionunclassified
“…The study which was done in 2011 in Iran under the title Perceived ethical values by Iranian nurses by Shahriari et al 9 showed that the Iranian nurses recognized the observance of ethical values essential to patient care, such as maintaining patient privacy, practice integrity, professional commitment, human relationships, justice, honesty and the promotion of professional competence. 9 Additionally, in a study which was done by Konishi et al 10 in 2009 under the title The Japanese Value of Harmony and Nursing Ethics, they found that the most important virtue for Japanese nurses in their studies who practice harmony was politeness, expressed by respect for the others, by touching the hearts of the people concerned, the nurses created the outcome of goodness, peace and growth of all members in the place, not limited to 'the patient good'. 10 It's noteworthy that the study which was done in Turkey under the title Burnout and Nurses' Personal and Professional Values by Altun 11 he concluded that the nurses' personal and professional values play an important role in the degree of burnout they experience.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the challenges faced by Iranian nurses affect their proper compliance with ethical standards in practice (10). These challenges are mostly caused by the shortage of nurses, job dissatisfaction, poor social status, and curriculum deficiencies about the subject of ethics (6,11), leading to consequences such as occupational burnout and increased job turnover (10). Nonetheless, an improved organizational climate can contribute to reducing these consequences.…”
Section: Introductionmentioning
confidence: 99%
“…which moral and ethical subjects take precedence over the protocols of patient care (6,7), and any negligence in observing nursing ethics can affect the best and most scientifically-based nursing care (8). In recent years, the subject of nursing ethics has attracted greater attention of the experts in this profession in Iran, and many researchers have conducted various studies in this regard.…”
Section: Introductionmentioning
confidence: 99%